Interneuron Heterotopia in the Lis1 Mutant Mouse Cortex Underlies a Structural and Functional Schizophrenia-Like Phenotype - Garcia-Lopez, Raquel; Pombero, Ana; Estirado, Alicia; Geijo-Barrientos, Emilio; Martinez, Salvador (Frontiers in Cell and Developmental Biology, 2021)
LIS1 is one of the principal genes related to Type I lissencephaly, a severe human brain malformation characterized by an abnormal neuronal migration in the cortex during embryonic development. This is clinically associated with epilepsy and cerebral palsy in severe cases, as well as a predisposition to developing mental disorders, in cases with a mild phenotype. Although genetic variations in the LIS1 gene have been associated with the development of schizophrenia, little is known about the underlying neurobiological mechanisms. We have studied how the Lis1 gene might cause deficits associated with the pathophysiology of schizophrenia using the Lis1/sLis1 murine model, which involves the deletion of the first coding exon of the Lis1 gene. Homozygous mice are not viable, but heterozygous animals present abnormal neuronal morphology, cortical dysplasia, and enhanced cortical excitability. We have observed reduced number of cells expressing GABA-synthesizing enzyme glutamic acid decarboxylase 67 (GAD67) in the hippocampus and the anterior cingulate area, as well as fewer parvalbumin-expressing cells in the anterior cingulate cortex in Lis1/sLis1 mutants compared to control mice. The cFOS protein expression (indicative of neuronal activity) in Lis1/sLis1 mice was higher in the medial prefrontal (mPFC), perirhinal (PERI), entorhinal (ENT), ectorhinal (ECT) cortices, and hippocampus compared to control mice. Our results suggest that deleting the first coding exon of the Lis1 gene might cause cortical anomalies associated with the pathophysiology of schizophrenia.